The legacy and songs of freedom [Bladmuziek]. - Connolly, James (Dublin : Socialist Party of Ireland, 1903)
Deze publicatie bevat volgende liederen
The dying Socialist to his Son
The Message
Arouse!
A Rebel Song
Freedom's Pioneers
The Flag
A Festive Song
Saoirse, a Ruin!
The Watchword
Freedom's Sun
"Be Moderate"
Hymn of Freedom
The Call of Erin
When Labour calls
Shake your Banners
O, Slaves of Toil!
A Father in Exile
Human Freedom
Engels
Bladmuziek
Keywords: liederen